Kenya Food Systems Conference Recommendations and actions to support the implementation of the Bottom-Up Economic Plan in Kenya - Rebecca Sarku; Stephen Whitfield (2023)
The workshop provided overview on the food systems landscape in Kenya, and to identify opportunities to inform inputs on crop diversification, livestock, land use expansion, and irrigation. It also contributed immensely into policy and stakeholder mapping exercise in Kenya.